Remittances and Education in Developing Countries - Ronaldo Nformi Taba Ndi; Francis Menjo Baye (Journal of Developing Economies, 2026)
Objective: Remittances are now a key source of funds for local and national development in developing countries – alleviating liquidity constraints, boosting consumption, investments, and savings. Previous studies reveal mixed results on the association between remittances and education, probably because of their failure to explore the nature of the relationship. To contribute to this literature, the following research question is posed: is the remittances-education link non-linear? We investigate the nature of the association between remittances and education. Method: We use data spanning 2000-2020 from 75 developing economies sourced from the World Bank and the United Nations Development Programme. The Driscoll & Kraay error-correction fixed-effects method is used for the analysis and refined using the System Generalized Method of Moments (SGMM) estimator. Findings: We find that remittances have a U-shaped relationship with educational attainment. For example, baseline SGMM results show that, below the threshold of about 20% of GDP, any unit increase in remittances is associated with dwindling levels of educational attainment, and above this threshold, any unit increase in remittances is associated with improvements in educational attainment. These results are qualitatively consistent across alternative methods, genders, regions, levels of income, and transmission channels– an indication of robustness. Originality/value: Unlike previous studies that assume linearity, this study introduces a threshold analysis to identify the level of remittances (% of GDP) where the effect on education shifts from negative to positive. Practical/Policy implication: These findings are supportive of public policies such as foreign exchange interventions that promote competition and innovation to boost the inflow of remittances and protect remittance recipients and their investments in education.